Identification of Novel Genetic Markers Based on DNA Polymorphisms and Their Application in Animal Production - Hsiu-Lin Huang; I-Yen Huang; Chia-Yu Lin; Mu-Chiou Huang (Research Advances in Microbiology and Biotechnology Vol. 7, 2023)
This study offers practical methods for locating new and conventional markers based on DNA polymorphisms. In modern medical research, genetic markers are a helpful tool for predicting disease risk and medication response. They can be used in animal research for diseases evaluation, gender determination, species identification, and marker-assisted selection. Numerous unique genetic markers in candidate genes have been discovered by combining DNA microarray technology and SNP (single nucleotide polymorphism) genotyping. In comparison to conventional breeding techniques, these markers have additional benefits since they may be used to accurately select animals and to quickly boost reproductive performance. The investigation of DNA polymorphisms employed modified random amplified polymorphic DNA (RAPD) or random amplified microsatellite polymorphism (RAMPO) fingerprinting, and the outcomes showed that innovative and stable markers may be used for identifying species and determining the gender of animals.